Adsorption of Acid Orange 8 Dye from Aqueous Solution Onto Unmodified and Modified Zeolites - Bertolini, Tharcila Colachite Rodrigues; Alcântara, Raquel Reis; Izidoro, Juliana de Carvalho; Fungaro, Denise Alves (Orbital: The Electronic Journal of Chemistry, 2015)
The adsorption of the acid dye Acid Orange 8 (AO8) onto unmodified and modified zeolites from coal fly ash and bottom ash was evaluated. The coal fly ash and bottom ash used in the synthesis of the zeolites by alkaline hydrothermal treatment were collected in the Thermoelectric Complex Jorge Lacerda, located in the Santa Catarina State, Brazil, the largest coal burning thermoelectric complex of Latin America. The modified zeolites were modiﬁed using the surfactant hexadecyltrimethylammonium bromide. The zeolitic materials were characterized predominantly as hydroxysodalite and NaX. The kinetics studies indicated that the adsorption followed the pseudo-second order kinetics. Linear and non-linear regression methods were used to determine the best fit of equilibrium data. The Freundlich model was better adjusted to the experimental data for all systems studied. The parameters of adsorption isotherms were used to predict the design of the equipment for performing adsorption discontinuous single stage.DOI: http://dx.doi.org/10.17807/orbital.v7i4.764